Creating Economic Opportunities: The Role of Labour Standards in Industrial Restructuring - Mazerolle, Maurice (Relations industrielles / Industrial Relations, 1995)
Creating Economic Opportunities: The Role of Labour Standards in Industrial Restructuring, edited by Werner Sengenberger and Duncan Campbell, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; International; Labor Unions; Labor economics; Labor relations; Labor standards; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z